Impact of CSR perceptions on workers' innovative behaviour: exploring the social exchange process and the role of perceived external prestige. (2019) - Gaudêncio, Pedro; Coelho, Arnaldo; Ribeiro, Neuza
The study aims to show how organisational corporate social responsibility (CSR) can influence workers' attitudes, especially in terms of innovative behaviour (IB). A second aim is to explore the social exchange process that may underlie this relationship, by examining the mediating role of organisational trust (OT), affective commitment (AC) and happiness (HAP), and the moderating role of perceived external prestige (PEP). The authors employ structural equation modelling based on survey data obtained from 315 Portuguese individuals. The findings show that perceptions of CSR predict IB through a social exchange process which involves the mediating role of OT, AC and HAP and the moderating process of PEP. They suggest that managers should implement CSR practices because these can contribute towards fostering IB, but that they should also invest in communication and in the process of upgrading corporate image. This study enriches the existing knowledge about social exchange relationships in organisational contexts, and responds to the need to understand underlying mechanisms linking CSR with workers' organisational outcomes, by analysing CSR practices from a holistic stakeholder perspective.